PERAN OLAHRAGA KOMUNITAS DALAM MEMBANGUN KOHESI SOSIAL DAN IDENTITAS KOLEKTIF MASYARAKAT PERKOTAAN - Ratna Humaira Khaerunnisa Fadhly; Acep Setiyawan; Adang Sudrajat (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
Community sports play a significant role in fostering social cohesion and strengthening collective identity within urban societies that are often characterized by diversity and individualism. In modern urban contexts, social interactions tend to be limited due to high mobility, work pressures, and fast-paced lifestyles. Community-based sports activities provide inclusive social spaces where individuals can interact, collaborate, and develop a sense of belonging across social, economic, and cultural differences. This literature-based study aims to examine the role of community sports in building social cohesion and collective identity in urban environments. The findings indicate that community sports function not only as physical activities but also as social platforms that encourage trust, solidarity, and civic participation. Regular and participatory sports activities help reinforce social bonds among individuals and foster a shared sense of community ownership. Furthermore, the symbols, values, and norms embedded in community sports contribute to the formation of a collective identity that reflects the character and pride of urban communities. Community sports also help reduce social fragmentation by creating egalitarian spaces for dialogue and interaction. Therefore, the development of community sports can be considered an effective social strategy for enhancing social cohesion and building sustainable collective identities in urban societies.